Fly as pollinator in Caralluma umbellata Haw. (Asclepiadaceae) found in the Pachamalai hills, Eastern Ghats, Tamil Nadu - Nandagopalan V; V, Anburaja; S, Prakash (Journal of Research in Biology, 2011)
Pollination studies have been done in the Caralluma umbellata, a member of Asclepiadaceae found in the Pachamalai hills of Tamil Nadu. The hills lie between latitudes 11°09’00" to 11°27’00" N and longitudes 78°28’00" to 78°49’00" E. The studies were carried out between April 2006 and April 2008. The main scope of the work was to investigate the pollination of the C. umbellata. Pollinator captures were carried out by (1) stalking near plants visually searching for arrival of probable pollinators and (2) random captures in the sampling area. The phenology of flowering is starting in the month of February and extended up to April. The fruit set is starting in the month of June onwards. The pollination in the C. umbellata is mainly done by house fly. A fleshy odour is produced during the peak flowering season. This odouring attracts the pollinator towards the flowers. The activity of the pollinator is almost peak during 14:15 hrs to 17:30 hrs. The time duration of the fly retaining in the flower is varied from few minutes to 25 minutes. The average time of the fly visiting the flower is 8.29 ± 7.98 minutes